(untitled) (Philological Studies, 2019)
The article deals with the interpretations of Man’s image as being drawn in the unique written document. The latter is a diary of a common peasant woman by the name Maria Petrovna Suslova from the village of Kamgort (Cherdyn’ district of Perm Region). The image of Man that has been created in her Diary is determined by the ancient type of thinking. It permits one to regard oneself as being the constituent part of Nature, thus not dominating in the surrounding world. Man in Suslova’s Diary is an acting creature. The activity of one is manifested in the labour. The latter implies the idea of the joint communal work of the people aimed to the provision of the society’s physical existence, but not creative activity of its separate member. M.P. Suslova’s Man is politically indifferent. The existing system of power in the country is of little interest for him. There are few references to political events in the Diary, besides these events are enumerated there in line with other occurrences, such as personal and everyday ones. On the whole, M.P. Suslova’s Diary is a unique source of various kinds of knowledge, the latter being of great historical and cultural values.